PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN FLIP CARD TERHADAP PEMAHAMAN KONSEP IPAS SISWA KELAS IV SD GUGUS VII KECAMATAN SUKASADA - Kadek Anisa; IG Agung Jaya Suryawan; Made Adi Nugraha Tristaningrat (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to identify significant differences in students' understanding of IPAS concepts between those taught using the CTL learning model supplemented with Flip Card media and those taught through the conventional model in grade IV at SD N Gugus VII, Sukasada District. This study was motivated by a clearly stated problem: inadequate understanding of the concept among fourth-grade students at SD Gugus VII, Sukasada District. The study employs constructivist and cognitive ideas. The research design used is a quasi-experimental design with a pretest-posttest control group framework. The study population consisted of 151 individuals, with a sample size of 64 children, comprising 31 fourth-grade students from SD N 1 Selat as the experimental class and 33 students from SD Negeri 5 Selat as the control class. Data collected in this study involved observation activities, interviews with classroom teachers, assessments, and documentation collection. The data analysis results were obtained using an independent t-test with an N-Gain value showing that the t-calculated score > t-table, i.e., 16.659 > 1.670. Hypothesis testing showed a Sig (2-tailed) score of 0.000 (p < 0.005), leading to the rejection of H0 and acceptance of H1. These results indicate a substantial disparity in understanding of IPAS concepts between students taught using the CTL teaching model with Flip Cards and students taught through the conventional teaching model in Grade IV of SD Gugus VII, Sukasada District, during the 2024/2025 academic year.